Anthropometric measurementrs of female adolescent ballet dancers - Lourens, Tanya (My University, 2012)
Introduction: Body composition assessment should be routine practice for health care professionals involved in ballet dancer health and wellness. It could serve as a tool to quantify appearance in dance in order to guide adolescent dancers towards appropriate body composition goals. The data obtained from body composition can be used to identify the “at risk dancer” and thus serve as a screening tool. Young dancers at risk to develop amenorrhea and possible osteoporoses later in life can be identified. The aim of this study was to investigate the body composition and somatotype of two groups of female adolescent ballet dancers, classified as having low – moderate training(< 10 hours per week) and those having moderate - high training(≥ 10 hours per week). The dancers who trained more or equal to 10 hours per week, were classified as Group one and the dancers who trained less than 10 hours per week, were classified as Group two. Methods: Fifteen subjects aged 13 – 18 years from Johannesburg and 39 subjects aged 13 – 18 years from Pretoria were invited to participate and volunteered for the study. All ethical procedures were conformed to. Anthropometric measurements were taken on all subjects and the data was used to compute percent body fat, body mass index and somatotype for each subject. Subjects completed a questionnaire pertaining to their demographic information, medical history, eating habits and training habits. Descriptive and inferential statistical methods were computed in order to determine variances, standard v deviations and means of the study population. Correlations between variables were also computed. Results: The two groups differed significantly with respect to mean arm girth (flexed), mean chest girth, mean biacromial breadth as well as body mass measurements. The group that trained more had higher measures for all components tested. The somatotypes of the subjects in Group one were predominantly localized in the endo-mesomorphic and endo-ectomorphic areas. Subjects in Group two were predominantly classified as ecto-endomorph. Conclusion: The study showed that there was no significant difference between the body composition of the group who trained less or equal to ten hours per week and the group who trained more than ten hours per week. The correlation results with respect to anthropometric data indicated that body mass, body mass index (BMI) and triceps skinfold measurements are the best measures to represent anthropometric data in female adolescent ballet dancers. The correlation results also indicated that body mass, BMI and percent body fat are not dependent on physical activity, but these variables might be more influenced by other factors, such as dietary intake.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of MSc(Med) in the field of Biokinetics. Johannesburg, 2012
Keywords: Anthropometry